Estimation of Motor Impairment and Usage of Upper Extremities during Daily Living Activities in Poststroke Hemiparesis Patients by Observation of Time Required to Accomplish Hand Dexterity Tasks - Tanaka, Tomoko (Biomed Res Int, 2019)
AIM: This study evaluated whether specific actual performance could accurately predict body function levels and upper limb use in the real-life functioning of poststroke hemiparesis patients to aid in choosing the most appropriate rehabilitation exercises. METHODS: We measured the time taken for poststroke patients to move small objects with the paralyzed hand and investigated how the measurement could estimate upper extremity motor impairment and hand usage during activities of daily living (ADL). We examined 86 stroke patients (age 66 ± 16 years) whose upper extremity motor paralysis was measured using the Fugl-Meyer assessment (FMA) and Southampton Hand Assessment Procedure (SHAP), and patient-reported ADL was investigated using the Jikei Assessment Scale for Motor Impairment in Daily Living (JASMID). To identify the time required to perform each SHAP item, we employed a linear regression analysis. The prediction formula was used in the linear regression analysis, and the coefficient of determination (R(2)) was applied to compare each component item score that was obtained with the predicted values derived from the linear regression analysis. RESULTS: The most easily accomplished task was Heavy Power in the SHAP. The R(2) between the SHAP Heavy Power item score and the FMA scores was moderate (R(2) = 0.344, P < 0.0001), whereas the R(2) with the JASMID score was low (R(2) = 0.126, P < 0.001). CONCLUSIONS: By measuring the time it takes for poststroke hemiparesis patients to hold and move an object, we developed a prediction formula for upper extremity motor function and hand dexterity.